Teachers’ Challenges In Implementing Formative Assessment In The Era Of Merdeka Curriculum - Ainun Zahro Hidayati; Moh Sahlan (PT. Education Research Center, 2026)
Formative assessment is one of the assessment types in the Merdeka Curriculum that plays an important role in continuously monitoring students’ learning progress. It is considered more effective as it provides feedback that can be used to improve the learning process. This study aims to identify the challenges faced by teachers in implementing formative assessment within the Merdeka Curriculum and to examine possible solutions to enhance its effectiveness. This research employs a library research method, drawing on relevant sources such as books, journal articles, and academic documents related to formative assessment and its implementation challenges. The findings reveal that teachers still face several obstacles, including limited understanding of the concept, difficulties in selecting appropriate assessment techniques, high administrative workload, low digital literacy, and inadequate facilities and infrastructure. Efforts to address these challenges include improving teacher competence, providing adequate facilities, and strengthening collaboration among schools, parents, communities, and the government, so that formative assessment can be implemented effectively and optimally to improve the quality of learning.